“Online Culture” - Luthfi Adam (Jurnal Komunikasi)
This article analyzes what exactly happened when someone “online” through his/her computer in Internet. This analysis will be based on Martin Heidegger’s existentialism and Don Ihde's philosophy of technology. Thus, online activity is seen as a contemporary culture, especially in urban society, which shows some particular characteristics.